Experimental Study of the Influence of Supplementary Reinforcement on Tensile Breakout Capacity of Headed Anchors in Nuclear Power Plant Equipment Foundations - Yang Xu; Chaoqun Chen; Minglei Xie; Jinxin Gong (Buildings)
Anchor bolts are often used in nuclear power plants to connect equipment and equipment foundations. Under a severe earthquake, tensile breakout failure is prone to occur in the anchor bolts. As the total amount of installed machines rises, the inertial forces transferred to the anchor bolts under seismic loads also increase significantly. Therefore, the capacity is no longer satisfied by concrete alone, and specialized supplementary reinforcement needs to be installed around the bolts. The study analyzed the tensile behavior of anchor bolts in foundations with supplementary reinforcement experimentally. A total of 16 single-headed anchors in RC foundations with various diameters, yield strengths, and forms of supplementary reinforcement were tested under monotonic tensile loading. The results show that supplemental tie bars and supplemental U-shaped bars, respectively, rely on the bond with the concrete and their own tensile strength to increase the tensile breakout capacity. Furthermore, based on the failure mechanism, a new model considering the terms of concrete resistance and reinforcement resistance for the tensile breakout capacity of headed anchors around with supplementary reinforcement was proposed. Compared with the strut–tie model by EN 1992-4:2018, the predicted results of the model proposed by this study are relatively consistent with the experimental results, while the results by EN 1992-4:2018 are overly conservative.